Helicobacter pylori y su relación con los factores de riesgo en estudiantes del Colegio Hernán Gallardo Moscoso - Correa Loján, Luis Geovanny (2015)
Infection by Helicobacter pylori occurs worldwide with a variation by age, geographic location, socioeconomic status of individuals and ethical differences. There is a risk of infection that affects to 50% of the world population. In the present investigation work it was necessary to determine the presence of Helicobacter pylori and its relationship with risk factors in students of Hernán Gallardo Moscoso High school of Loja city; and to establish the main risk factors for contracting Helicobacter pylori; to determine the presence of Helicobacter pylori in feces the students of Hernán Gallardo Moscoso High school and, to relate the presence of Helicobacter pylori with major risk factors through a descriptive and cross-sectional study in a sample of 114 students of the basic and diversified cycles attending the school and who met the inclusion criteria and exclusion. For the analysis of Helicobacter pylori Immunochromatography technique was applied because this is a modern method with a sensitivity and specificity significant currently used for the fast diagnosis of Helicobacter pylori with the following conclusions: that 52% of the studied population had positive Helicobacter pylori. According to the risk factors determined by a survey, it was found that 93% of students do not know about the infection of Helicobacter pylori; 73% have contact with domestic animals, 83% do not wash their hands before meals, 76% did not wash their hands after using the toilet and 52% eat out. Relating risk factors with 59 Helicobacter pylori positive patients, it was found that knowledge about Helicobacter pylori has 86.4%, do not wash their hands before every meal 76,2% and, do not washed hands after going to the toilet in 83%, being these the most predisposing factors in this study. So it should be necessary to encourage students for having a healthy diet and for maintaining hygiene to improve the quality of life of people. Keywords: Helicobacter pylori, risk factors, technical immunochromatography.